Transformational Leadership as a Catalyst for Professional Work Culture in Islamic Boarding Schools - Didi Sartika; Andika Hariyanto Surbakti; Ansori Ansori; Halimatus Sya'diyah (Indonesian Journal of Education and Social Studies, 2025)
This research aims to examine in depth how transformational leadership is carried out by Islamic boarding school principals in forming a professional work culture in a traditional Islamic education environment. Using a qualitative approach of a case study, this study explores the strategies, dynamics, and impact of leadership on institutional change. Data was collected through in-depth interviews, observations, and analysis of institutional documents. The results of the study show that the head of the pesantren plays a key role as an agent of change through three main approaches: (1) digitalization-based structure and management, (2) strengthening human resources through the ustaz regeneration system and continuous evaluation, and (3) internalizing the Islamic values of Aswaja into the professional work practices of students and staff. These three aspects encourage the formation of a collaborative, accountable, and quality-oriented work culture. This research confirms that transformational leadership is not only effective in the context of modern management, but also able to adapt to the religious values of Islamic boarding schools. The practical implication of this research is the need to develop a value-based and innovative leadership model in Islamic educational institutions, which emphasizes not only spiritual attainment but also institutional effectiveness professionally.